Karakteristik Kimia Kulit Lumpia Basah dengan Fortifikasi Tepung Tulang Ikan Patin (Pangasius pangasius) - Junianto, Junianto; Hasibuan, Linda Naomi; Rostini, Iis; Pratama, Rusky Intan (Faculty of Agricultural Technology, University of Jember, 2024)
Waste from patin fish (Pangasius pangasius) consumption is skin and fish bone. Its waste generally used as a raw material for food and industrial products because of fat, gelatin, collagen, and calcium compounds. Based on its calcium compound, another food application is the fortification of patin fish bone on wet spring roll wrapper. It is important to increase the consumption rate of calcium nutrition. Therefore, this research aimed to improve the proximate composition (especially calcium) of wet spring roll wrapper with 6% catfish bone flour fortification. The method used in this research was experimental with two treatments, i.e. the addition of 6% patin fish bone flour (A1) and 0% patin fish bone flour (A0) as a control. The parameters observed were moisture, ash, fat, protein, carbohydrate, and calcium content. The test procedure for each parameter observed is based on SNI 01-2354:2006. Sample testing was carried out in duplicate. The proximate composition of wet spring roll wrapper fortified with 6% patin fish bone flour consists of moisture, ash, fat, protein, carbohydrate, and calcium content respectively 60.21%, 2.61%, 0,71%, 3.96%, 32.51%, and 19.90 mg/100 g. Wet spring roll wrapper that was fortified with 6% patin fish bone flour (A1) had higher calcium content (19.90 mg/100 g) compared to wet spring roll wrapper with no fortification (control/A0) of the patin fish bone flour (8.22 mg/100 g). The moisture content of this calcium-rich wet spring roll wrapper is included in the Indonesian National Quality Standard (SNI) number 2987-2015 for wet noodles. This wet spring roll wrapper is one of diversified product using fishbone fortification to increase its calcium content. Keywords: fish bone, calsium, consumption, protein, waste